Catalogus ad collectionem Materiae Medicae in Academia Georgia Augusta Katalog der Pharmakognostischen Sammlung der Georg-August-Universität Göttingen - Wissemann, Volker (Universitätsverlag Göttingen, 2017)
In the attic of the botanical institute of the Georg-August University of Göttingen, a pharmacognostic collection was stored for over sixty years, packed in about 50 boxes: a document of a discipline that was represented by the institute until 1938. The collection comprises about 8,000 samples and objects from of materia medica from the 19th and early 20th centuries; it is thus one of the few university collections to have been preserved in almost its entirety - a comparison with contemporary textbooks and pharmacopoeias shows that almost all common drugs are included in numerous variants. The preserved collection samples show that it is not only a scientific reference collection to this day, but that the collection has at the same time taken on important functions in research and teaching including education. Parallel to the cataloguing, the history of the collection was reconstructed in rudimentary form, and natural and cultural studies were carried out on some of the holdings. cultural studies were carried out on some of the holdings. In the process, it became increasingly clear that the potential of the collection as a source material and basis for a large number of studies in the history of science and the natural sciences is considerable; by presenting the collection and its history, we hope to stimulate such studies. Prof. Dr. Volker Wissemann is Professor of Special Botany at the Justus Liebig University of Giessen, Director of the Institute of Botany incl. the Herbarium, Condirector of the Hermann Hoffmann Academy and Scientific Director of the Giessen Botanical Garden. He is a member of the Göttingen Academy of Sciences and Göttingen and alumnus of the Georgia Augusta. Prof. Dr. Kärin Nickelsen is professor of the history of science at the Department of History at the Ludwig Maximilian University in Munich. She is a member of the National Academy of Sciences (Leopoldina) and an alumna of the Georgia Augusta. (translated with DeepL)